Effects of precipitation and temperature on the species composition and pollinator efficiency of ocimum kilimandscharicum flower visitors in Kakamega forest ecosystem - HM Tsingalia; Mandela HK (Open Journal of Environmental Biology - Peertechz Publications, 2023)
Pollination, a critical ecosystem service in the maintenance of biodiversity is on the decline due to several factors including habitat loss, exotic pest invasions, pollution, overharvesting, climate, and land use changes. This study analyzed flower visitors' activity of Ocimum kilimandscharicum in the Kakamega forest. Specifically, the study sought to: (i) assess the effects of temperature and precipitation on flower visitors' diversity and (ii) identify the most efficient flower visitor using seed set analysis. Data on pollinators were collected through direct observation and sweep-netting and the bagging method in which, flowers were covered using a pollinator bag pre-anthesis and allowed a single visit from a flower visitor. Seed sets from the flowers were collected and counted. Six study sites were identified along two transects each 2.5 km long and labeled A to F. Sampling was done from 7:30 am to 4:00 pm, three days a week for five months consecutively. Secondary data on bee species and their characteristics were used in identification. There were no significant correlations between temperature and diversity (r = -0.509, p = 0.3810), precipitation and diversity (r = 0.377; p = 0.531), temperature and species abundance (r = -0.00618; p = 0.9921), species abundance and precipitation (r = -0.248; p = 0.688), temperature and the species richness of flower-visiting insects (r = -0.729 p = 0.1623) and between precipitation and species richness (r = 0.824; p = 0.08592). The highest number of seed sets, 12,944 was collected under the Apis mellifera making this species, the most efficient pollinator. This study clearly shows that Ocimum kilimandscharicum flower visitors are important in pollination where the higher number of visits translates into higher numbers of seeds set.